ANALYSIS OF ATMOSPHERIC AIR OF SURKHONDARYO REGION USING PHYSICO-CHEMICAL METHODS - Niyozova, Oyimxol; Turayev , Khait; Jumayeva , Zulkhumar (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
It is very important to study the environmental problems in the southern regions of Uzbekistan and the harmful effects caused to people, animals and plants. Atmospheric air pollution, sudden warming and drying of the air affect the environment and ecological system. Therefore, it was aimed to study polluted atmospheric air, dry and hot atmospheric air, dry soil temperature, and the amount of methane and carbon dioxide gas in the air.